Rawls and Habermas : reason, pluralism, and the claims of political philosophy - Hedrick, Todd, 1978- (Stanford University Press, 2010)
A critical evaluation of Rawlsian and Habermasian paradigms of political philosophy that offers an interpretation and defense of Habermas's theory of law and democracy as a superior alternative to Rawls's political liberalism.